Novel application of silica materials to reduce phenolic content of red wines - Alessandro Manzoni; Sara Muñoz-Pina; Édgar Pérez-Esteve; Victoria Lizama; María J. García; Angel Argüelles; Jose Luis Aleixandre-Tudo (Applied Food Research)
Phenolic compounds are responsible for the most critical attributes of red wine quality. Structural changes at the molecular level influence the ability of phenolics to contribute to the colour, astringency, and bitterness of the wines. Modulating the phenolic content of red wines might lead to improved mouthfeel properties and enhanced quality. A novel approach using hybrid organic-inorganic systems in the form of functionalised silica materials able to reduce target molecules is presented in this work. Therefore, this study investigates the ability of amine and thiol functionalised silica materials to reduce red wine phenolic content. For this, wines made with Cabernet Sauvignon and Bobal grapes harvested at two different ripening levels were used. Silica fumed was functionalised with two trialkoxysilane derivatives exhibiting thiol or amine moieties. The results showed the ability of the amine and thiol functionalised silica materials to reduce the phenolic content of the wines produced. The anthocyanin and tannin content showed a 30.7 % and 20.9 % reduction in Cabernet Sauvignon wines made with riper grapes and treated with the thiol functionalised material. Moreover, the amine functionalised material caused a 7.4 % and 34.1 % decrease in the anthocyanin and tannin content of Bobal red wines from grapes harvested at the first ripening point. The materials showed varying abilities to interact between the different phenolic families (anthocyanins vs. tannins).